Administration of dietary recombinant hepcidin on grass carp (Ctenopharyngodon idella) against Flavobacterium columnare infection under cage aquaculture conditions. Issue 99 (April 2020) - Chen, Tong; Zhou, Jiancheng; Qu, Ziling; Zou, Qi; Liu, Xiaoling; Su, Jianguo; Fu, Xiaozhe; Yuan, Gailing
Abstract: Hepcidin links iron metabolism with innate immunity during the inhibition of bacterial infection. Our previous studies had shown that recombinant hepcidin can significantly reduce the mortality rate of Ctenopharyngodon idella infected with Flavobacterium columnare under laboratory conditions. Here, we studied the preventive and therapeutic effects of feed supplemented with different doses of recombinant hepcidin on F. columnare -challenged C. idella reared in a cage culture environment. The results showed that in the prevention groups, 30 and 90 mg/kg of added purified and unpurified hepcidin respectively resulted in a higher survival rate in the early post-infection period, while 60 mg/kg of purified hepcidin significantly improved the survival rate in the therapy group (all compared to the control group). In the hepatopancreas, the expression of hepcidin and ferritin was significantly up-regulated, and the levels of ferroportin and serum iron were significantly decreased, especially in the therapy group. In addition, the expression of iron-related genes in spleen and intestine exhibited a similar trend to that in hepatopancreas. Meanwhile, immune genes were up-regulated to varying degrees, and the therapy group exhibited a significantly improved expression of pro-inflammatory cytokines and specific immunity. In summary, our study shows that different doses of recombinant hepcidin had protective effects against bacterial infection by regulating the iron distribution and immune gene expression, which provides a strong foundation for the application of recombinant hepcidin in aquaculture. Highlights: Dietary recombinant CiHep has protective effect on C. idella challenged with F. columnare under cage aquaculture conditions. Dietary recombinant CiHep increased combined iron levels in hepatopancreas and spleen, while decreasing the serum iron. The addition of 60 mg/kg Hepcidin to diet could improve the immune indexes of C. idella after infection with F. columnare.